American Melancholy : Constructions of Depression in the Twentieth Century - Hirshbein, Laura D., 1967- (Book collections on Project MUSE., 2009)
"Depression was not classified as a disease until the 1980 publication of the American Psychiatric Association's Diagnostic and Statistical Manual-III (DSM-III). How, then, is it that such an illness, thought to affect between 14 and 17 million Americans, was not specifically defined until the late twentieth century?" "Laura D. Hirshbein traces the growth of depression as an object of medical study and as a consumer commodity and illustrates how and why depression came to be such a huge medical, social, and cultural phenomenon. This is the first book to address gender issues in the construction of depression, explore key questions of how its diagnosis was developed, how it has been used, and how we should question its application in American society."--Jacket